A decision support model to manage overspecification in system development projects. (3rd July 2021) - Shabi, Jacob; Reich, Yoram; Robinzon, Roni; Mirer, Tania
Abstract : Good quality products are developed to satisfy the needs of their customers and gain their satisfaction. This could be attained by delivering products embedding only features that really meet customer's needs and reduce cost. Unfortunately, many products are plagued with overspecification that lead to complicating the design and marketing of products with characteristics or functions neither really necessary nor desired by customers or the market and are unnecessarily expensive. This paper presents a model to identify and manage overspecification in system development projects. It mainly focuses on large-scale systems development, specified by the customer, rather than the design of consumer goods that follow market research. First, an optimisation problem with project constraints to mitigate the impacts of overspecification is formalised and subsequently, a practical model to manage overspecification in projects is presented and demonstrated on a case study.